A Case Study Examination of Georgia Early College Students’ Perceptions Related to College Readiness - Harrell, Angela Chante (My University, 2022)
This case study examined the student perceptions of their time in one of Georgia’s Early College High Schools as related to their confidence in preparation for college. The mixed method design allowed for a look into the experiences of both recent graduates and current students. This Early College High School campus is one of eight in the state of Georgia. This campus targets a diverse population of first-generation college students and enrolls them in a program that is located physically adjacent to the public state university campus. Traditionally, many of the students who are enrolled in this program would not be expected to continue into postsecondary education and the population of the Early College campus is representative of communities that are not well represented in college campus environments. Recent graduates were interviewed using an in-depth approach via Google Meet. For phase two of the study, students who are currently enrolled in the Early College were offered a survey. This survey included items related to student perception, college readiness and additional topics of interest that arose from the phase one interviews. Three key findings resulted from the analysis of this research study. First, students’ perception of family engagement was more highly correlated with college readiness confidence than either the perception of academic preparation or social engagement. Second, students who noted a perception of positive academic preparation were also likely to perceive positive social engagement. Finally, while both current students and recent graduates perceived a high degree of self-advocacy within the Early College model, they described less certainty about relying on self-advocacy after their time in the Early College setting. Keywords: Early College, First Generation College
CHAPTER 1 1 -- Introduction 1 -- Problem Statement 3 -- Purpose and Scope 5 -- Research Questions 7 -- Theoretical Framework 8 -- Methods 9 -- Research Design 9 -- Data Collection Procedures 10 -- Data Analysis Procedures 12 -- Significance 15 -- Terms and Definitions 15 -- CHAPTER II 18 -- Characteristics of Students Joining ECHS 18 -- Early College High School Initiative 21 -- Conley’s Four Keys Model of College Readiness 24 -- College Transition Knowledge and Skills 25 -- Culture of College 29 -- Self-Advocacy 30 -- College Enrollment Knowledge 32 -- Alternative Frameworks 34 -- Student Perceptions of ECHS Experience 36 -- Academic Preparation 37 -- Social Engagement 37 -- Family Relationship to School 37 -- CHAPTER III 39 -- Research Design 39 -- Research Participants 40 -- Case Selection 40 -- Student Characteristics at the ECHS 40 -- Phase 1 Interview Participant Recruitment 42 -- Interview Participant Demographics 43 -- Phase 2 Survey Participant Recruitment 45 -- Survey Participant Demographics 46 -- Instruments 48 -- Recent Graduate Interview 48 -- Current Student Survey 50 -- Data Collection Procedures 51 -- Phase One: Recent Graduate Interview 51 -- Phase Two: Current Student Survey 54 -- Data Analysis Procedures 55 -- Phase One: Recent Graduate Interview 55 -- Phase Two: Current Student Survey 57 -- Descriptive Statistic Analysis 59 -- Correlation Coefficients 59 -- Validity and Reliability 60 -- Validity 60 -- Reliability 60 -- Constraints 61 -- Limitations 61 -- CHAPTER IV 63 -- Student Perceptions of ECHS Experience (RQ1) 63 -- Academic Preparation in ECHS 63 -- Social Engagement in ECHS 71 -- Family Relationship with ECHS 79 -- Summary of RQ1 Findings 84 -- Student Confidence in College Transition Knowledge and Skills (RQ2) 85 -- Awareness of College Culture 85 -- Self-Advocacy 89 -- College Enrollment Knowledge 94 -- Interview Themes’ Influence on Phase Two Survey 96 -- “As Prepared for College as I Would Be in Another School” 97 -- “Feels Like Family” 97 -- “Comfortable Right Away” 97 -- Summary of RQ2 Findings 98 -- Relationship Between ECHS Experience and Confidence (RQ3) 99 -- Changes Made to the Survey Based on Interview Findings 100 -- Descriptive Analysis Results 100 -- Student Perception 101 -- Student Confidence 104 -- Correlational Analysis Results 105 -- Student Perception about the ECHS Experience 106 -- Student Confidence in College Transition Knowledge and Skills 106 -- Student Perception and Confidence 107 -- Summary of RQ3 Findings 108 -- CHAPTER V 110 -- Conclusions and Discussion 110 -- Family Relationships are Key in the ECHS 115 -- Social Engagement is Meaningful for ECHS Students 118 -- Teaching Self-Advocacy is Preferred to Simply Advocating 119 -- Implications for Practice 121 -- A Strong Family Relationship With the School 121 -- Students Utilized Their Voice to Improve Focus on Social Engagement 123 -- A Gradual Release of Responsibility for Self-Advocacy 124 -- Implications for Research 125 -- Summary 126 -- REFERENCES 128
Keywords: College preparation programs; College-school cooperation; Curriculum development; Dissertations, Academic--United States; Education; First-generation college students; Georgia; High school students; College students